Providing Person-Centered Care via Telemedicine in the Era of COVID-19 in Multiple Sclerosis - Abbatemarco, Justin R (J Patient Exp, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has catalyzed the rapid adoption of telemedicine which encompasses synchronous and asynchronous interactions between patients and providers. In order to facilitate this rapid deployment, there has been numerous regulatory changes to ensure caregivers can effectively communicate with patients during this time. We illustrate a model where people, processes, and technology work together to address the comprehensive needs of multiple sclerosis (MS) patients. We provide a template for how multidisciplinary, academic practices can implement a rapid shift to virtual management during the pandemic using existing infrastructure that can be widely adopted to care for patients with chronic diseases. Telemedicine was incorporated into our entire practice, which encompasses neurology, rehabilitation, advanced practice providers, fellows, social work, and behavioral medicine. Our patient satisfaction results remained stable across almost all domains when compared to survey results from our typical, in-office visits. Our experience demonstrates telemedicine’s transformative potential in successfully managing a multidisciplinary MS clinic during the time of a pandemic and outlines a potential path for other practices to follow.